Dinamika Interaksi Orang tua-Anak dan Dampaknya dalam Membentuk Perilaku Sosial Anak Usia 11-15 tahun - Sawaludin, Vicky Purwadi Putra; Madania, Madania; Amala, Saniyya Khoirun; Athiyallah, Arina (Universitas Al Azhar Indonesia, 2026)
Parent–child interaction during the social development stage of children aged 11–15 plays a crucial role in shaping social skills. This study employed a qualitative approach with a case study method involving three families in Karawang, Madura, and Boyolali. The subjects consisted of fathers, mothers, and children (a total of nine participants) with children aged 11–15, selected through purposive sampling. Data were collected through semi-structured interviews and limited observation. Validity was ensured using source triangulation, technique triangulation, and member checking. Data analysis followed a thematic approach based on Miles and Huberman’s model, including data reduction, data display, and reflective conclusion drawing. The findings revealed five main themes: (1) emotional relationships between parents and children; (2) daily activities and togetherness; (3) family decision-making; (4) parenting styles and family values; and (5) children’s social relationships. Authoritarian parenting produced obedient but withdrawn children, permissive parenting provided freedom but weakened structure, while authoritative parenting—balancing firmness, warmth, and spiritual values—shaped children to be more confident, empathetic, and adaptive. Democratic parent–child interaction with emotional involvement was proven to support social development in children aged 11–15. The implications suggest that families need to strengthen open communication and value-based parenting, schools and communities should provide spaces for children’s participation, and public policy should encourage responsive parenting programs.Keywords - Authoritative Parenting Style, Children’s Social Behaviour, Emotional Involvement, Family Education, Parent–Child Interaction.